Penanaman Stek Pucuk Tanaman Nilam (Pogostemon cablin benth) dengan Teknik Sungkup Menggunakan Gelas Plastik: Sahlim, S.ST - Sahlim , S.ST (Sumber Penyuluhan Pertanian Indonesia, 2023)
This study aims to determine the effect of the application of containment time on the survival percentage of direct growers of patchouli cuttings (Pogostemon cablin Benth) using the plastic glass lid technique.The experiment was carried out at the Sipakabaji Farmers Group Head's Garden, Watuliu Village, Lasusua District, North Kolaka Regency. Trial starts from November to December 2021.This study was structured using a Randomized Block Design (RAK) consisting of five treatments and five replications. The treatment is as follows: P0 (Control) without being covered; P1 was confined for 5 days; P2 was confined for 10 days; P3 is covered for 15 days; and P4 were covered for 20 days. Treatment on P3 covered for 15 days gave a good effect on the percentage of live plants and on plant height. The contribution of P3 treatment resulted in the percentage of plants growing 100 percent.